NADPH oxidase-mediated induction of reactive oxygen species and extracellular matrix deposition by insulin-like growth factor binding protein-5 - Yasuoka, Hidekata (Am J Physiol Lung Cell Mol Physiol, 2019)
Insulin-like growth factor binding protein-5 (IGFBP-5) induces production of the extracellular matrix (ECM) components collagen and fibronectin both in vitro and in vivo and is overexpressed in patients with fibrosing lung diseases, such as idiopathic pulmonary fibrosis (IPF) and systemic sclerosis (SSc). However, the mechanism by which IGFBP-5 exerts its fibrotic effect is incompletely understood. Recent reports have shown a substantial role of reactive oxygen species (ROS) in fibrosis; thus we hypothesized that IGFBP-5 induces production of ROS to mediate the profibrotic process. In vitro analyses revealed that ROS production was induced by recombinant and adenoviral vector-mediated IGFBP-5 (AdBP5) in a dose- and time-dependent manner, regulated through MEK/ERK and JNK signaling, and primarily mediated by NADPH oxidase (Nox). Silencing IGFBP-5 in SSc and IPF fibroblasts reduced ROS production. The antioxidants diphenyleneiodonium and N-acetylcysteine blocked IGFBP-5-stimulated ECM production in normal, SSc, and IPF human primary lung fibroblasts. In murine fibroblasts lacking critical components of the Nox machinery, AdBP5-stimulated ROS production and fibronectin expression were reduced compared with wild-type fibroblasts. IGFBP-5 stimulated transcriptional expression of Nox3 in human fibroblasts while selective knockdown of Nox3 reduced ROS production by IGFBP-5. Thus IGFBP-5 mediates fibrosis through production of ROS in a Nox-dependent manner.